Leptin Influence Cholelithiasis Formation by Regulating Bile Acid Metabolism - Wen, Jian; Jiang, Yu; Lei, Zhengming; He, Jingyu; Ye, Mingxin; Fu, Wenguang (Turkish Journal of Gastroenterology, 2021)
Background: Bile acid metabolism is a contributing factor that promotes cholelithiasis. Recent studies have suggested novel roles of leptin in the formation of gallbladder stones (GS); however, no evidence confirmed the function of leptin in the formation of primary intrahepatic bile duct stones (PIBDS) . In the current study, the liver tissues of patients with GS and PIBDS were collected to check the mRNA and protein expression levels of BSEP. Methods: L02 cells stimulated with leptin were served for the expression of OB-Rb, AMPKα2, and BSEP by quantitative-polymerase chain reaction (q-PCR), Western blot, and immunohistochemistry, respectively. Results: The results showed that the level of serum leptin was higher in the GS group than in the control and PIBDS groups. Compared with the control group, the expression levels of OB-Rb, p-AMPKa2, and BSEP decreased significantly in the GS and PIBDS groups. In vitro, compared with the control cells, the protein levels of OB-Rb, p-AMPKa2, and BSEP increased in the L02 cells cultured with leptin. However, these enhancements disappeared when the cells were co-cultured with leptin plus Compound C. Conclusion: The present results suggest that cholelithiasis, especially the formation of PIBDS, was connected with leptin, which could regulate bile acid metabolism through the OB-Rb/AMPKa2/BSEP signaling pathway.